Potensi Komersialisasi Produk Pulsing Bunga Mawar (Rosa hybrida) Potong Segar untuk Peningkatan Nilai Tambah - , SHYNTIA ATICA PUTRI; , Dr. Ir. Dyah Ismoyowati, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Pulse treatment is treatment carried out on flowers by immersing the tip of the rod with a preservative solution containing nutrients and germicides. Treatment is done to make longer shelf life in order to anticipate demand and supply fluctuations. In the present study, pulse treatment carried out on cut roses. The research objective is to identified the consumers of cut roses, to test the technical performance, financial, and consumer preference of pulse treatment for cut roses, and create a pulsing product which technically feasible, financially, and accepted by the market. The final result of the emphasis is commercialization of pulsing product. The market identification result was freshness as the most important criteria for cut roses. Pulse treatmentâs alternatives were P1 (5% sucrose+20 mg/l AgNO3), P2 (150 mg/l AgNO3), P3 (1,2% sucrose+0,2 mM STS), P4 (5% sucrose+20 mg/l AgNO3+320 mg/l citric acid), P5 (1,2% sucrose+ 0,2 mM STS+ warm water (40 0 C)), P6 (5% sucrose+20 mg/l AgNO3+320 mg/l citric acid+warm water (40 0 C)). Based on freshness, stem texture, and color of petals, the choosen was P1 with 8 days shelf life. Next step was consumer preferences testing for alternatives pulse treatment P1-P6 based on freshness, shelf life, and color of petals. The choosen alternative was P1 with priority weight 0,3736 and freshness as the most important criteria. Financial performance is done by calculating the cost of each pulse treatment and compare the obtained results. Selected alternative was P1 with cost Rp 800,00 which capable of providing shelf life of 8 days. Based on laboratory test, consumer preferences, and financial performance, the alternative that will made was P1 with powders and solution form. The consumers prefer pulsing powder rather than pulsing solution for a price of Rp 1.800,00 per liter of water used to provide a shelf life of 8 days, no different result by pulsing solution at a price of Rp 12.800,00.